Pengaruh Pelatihan Forgiveness terhadap Penurunan Tingkat Kemarahan Remaja yang Tinggal di Panti Asuhan - Ratna Wulandari; Sri Muliati Abdullah; Kondang Budiyani (Jurnal Psikologi, 2023)
ABSTRACTThis study aims to determine the differences in the level of anger among adolescents who live in anti-care treatment before and after forgiveness training. The method used in this study was a non-randomized control group with a pretest-posttest design and measured three times (pretest, posttest, and follow-up). The subjects of this study were 10 adolescents in the orphanage and had anger scores in the high and medium categories. Subjects were divided into experimental group and control group. The experimental group was given treatment in the form of a forgiveness training intervention. The measuring instrument used to see the anger score of adolescent orphanages using State-Trait Anger Expression Inventory-2 (STAXY-2). The data analysis technique used is the Mann Whitney U-Test analysis technique. Result analysis (p = 0.008 <0.05), meaning that there is a difference in the anger score of adolescents in the orphanage after being given a forgiveness training intervention compared to the control group, where the level of anger in the experimental group after being given the intervention was lower than the control group. Based on the explanation above, it can be concluded that forgiveness training can reduce anger in adolescents living in orphanages.